A comprehensive review on batteries and supercapacitors: Development and challenges since their inception. Issue 1 (6th April 2022) - Dutta, Arindam; Mitra, Shirsendu; Basak, Mitali; Banerjee, Tamal
Abstract: The chemistry underlying the storage phenomena in batteries and supercapacitors has been known to mankind for quite some time now. Nonetheless, a holistic apprehension of their rudimentary characteristics throughout their lifetime and beyond is imperative to accentuate their maximum potential. Although numerous reviews have addressed many of the facts individually, a consolidated report on the associated history, challenges, and environmental aspects considering the cutting‐edge advancements in this field is missing. This review gives a comprehensive insight into the two technologies by drawing a detailed comparison between their governing attributes and potential challenges. First, a brief history of batteries and supercapacitors along with their classifications based on materials and corresponding working mechanisms are delineated. Thereafter, some of the inexorable losses restricting the performance of these systems from reaching their theoretical limits are outlined. A picture of the significance of theoretical modeling of batteries and supercapacitors highlighting the associated challenges in the same is drawn. Furthermore, their fates after retirement as well as their scopes in the future based on their current trends are reported in the ensuing sections. Alongside detailed tutorial background of energy storage literature, this review compares different energy storage devices and the latest developments in this field. Abstract : The differences between batteries and supercapacitors have created a niche for the two technologies to sustain concordantly in various applications. The development of newer materials and techniques has led them to evolve constantly over time. With further comprehension of their intrinsic characteristics and environmental footprint through theoretical and experiential analysis, these technologies are expected to dominate the field of energy storage for decades to come.